2014
DOI: 10.1002/uog.14660
|View full text |Cite
|
Sign up to set email alerts
|

Practical approach to obtain the mid‐sagittal plane of the fetal face at 11–13 weeks' gestation by two‐dimensional ultrasound

Abstract: Practical approach to obtain the mid-sagittal plane of the fetal face at 11-13 weeks' gestation by two-dimensional ultrasound

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Other authors identified ultrasound landmarks to be focused on at the time of plane acquisition for fetal biometry, for example in the context of nuchal translucency measurement 18 . This was found to improve reproducibility and image quality.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors identified ultrasound landmarks to be focused on at the time of plane acquisition for fetal biometry, for example in the context of nuchal translucency measurement 18 . This was found to improve reproducibility and image quality.…”
Section: Discussionmentioning
confidence: 99%